Analysis of regioisomers of polyunsaturated triacylglycerols in marine matrices by HPLC/HRMS. (1st January 2015) - Baiocchi, Claudio; Medana, Claudio; Dal Bello, Federica; Giancotti, Valeria; Aigotti, Riccardo; Gastaldi, Daniela
Highlights: Comparison of thermal induced and CID MS/MS TAG fragmentation in marine oils. Development of HPLC–HRMS 2 method to characterise fatty acids in sn-2 position. MS 3 experiments to clear out the discrepancy between thermal and CID fragmentations. Determination of TAGs structure in tuna and algae oils. Evaluation of content of ω-3 fatty acids in tuna and algae oils. Abstract: Natural sources of triacylglycerols containing ω-3 fatty acids are of particular interest due to their protective role against several human diseases. However, as it has been well ascertained, the position of the ω-3 fatty acid on the triacylglycerol backbone influences how digestion occurs. In particular, occurrence at the sn-2 position allows optimal intestinal absorption conditions. The analytical protocol for regioisomer characterisation of fatty acids in a triacylglycerol usually requires the use of stereospecific lipases before instrumental identification. In this paper, we propose a more direct instrumental determination of triacylglycerol composition along with sn-2 positional identification of the fatty acids constituents by Liquid Chromatography–High Resolution Mass Spectrometry. Different intensities of product signals obtained in MS 2 and MS 3 experiments were used to define an interpretative scheme able to rationalise the stereochemistry of the TAGs. Marine matrices like tuna and algae oils have been studied in detail, their triacylglycerols identified and sn-2 positional arrangement of fatty acid constituents assessed.